2015
DOI: 10.1088/0004-637x/811/1/24
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Inner Knot of the Crab: The Site of the Gamma-Ray Flares?

Abstract: One of the most intriguing results from the γ-ray instruments currently in orbit has been the detection of powerful flares from the Crab Nebula. Such events, with a cadence of about one per year, can be so dramatic as to make the system the brightest source in the γ-ray sky as occurred in 2011 April. These flares challenge our understanding of pulsar wind nebulae and models for particle acceleration. To pinpoint the production site(s) within the Nebula, a multiwavelength campaign has been carried out using Kec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 47 publications
6
50
0
Order By: Relevance
“…As we have discussed, for the parameters of the Crab wind this dissipation leads only to plasma heating (Sec.2.2) and the downstream magnetization is too low to make gamma-ray flares via reconnection of the residual magnetic field. The observations of the inner knot of the Crab nebula, which is best explained as a Doppler-boosted emission of the shocked striped wind (Lyutikov et al 2016), agree with this verdict -its optical and IR emission does not correlate with the gamma-ray flares (Rudy et al 2015).…”
Section: Magnetization In Different Parts Of the Nebulasupporting
confidence: 60%
See 2 more Smart Citations
“…As we have discussed, for the parameters of the Crab wind this dissipation leads only to plasma heating (Sec.2.2) and the downstream magnetization is too low to make gamma-ray flares via reconnection of the residual magnetic field. The observations of the inner knot of the Crab nebula, which is best explained as a Doppler-boosted emission of the shocked striped wind (Lyutikov et al 2016), agree with this verdict -its optical and IR emission does not correlate with the gamma-ray flares (Rudy et al 2015).…”
Section: Magnetization In Different Parts Of the Nebulasupporting
confidence: 60%
“…This knot is resolved and has the size similar to that of the X-ray knots. The knot is not seen in the radio and X-ray bands (Rudy et al 2015). In addition to these features, there are also fine bright arc-like filaments ("wisps") originating in the vicinity of the inner ring and moving away from it with speeds up to 0.7 c..…”
Section: The Nebulamentioning
confidence: 95%
See 1 more Smart Citation
“…Since then, both the telescopes continue recording such flares approximately once in a year, the strongest of them (super-flare) having been detected in April 2011 [3], [4]. The energy spectra of additional emission during the flares were measured to be different from those of the Nebula, however, "the mechanism driving the flares, their impulsive nature, the 12-month recurrence time, and the location, remain unknown" [5]. For all that, based on multi-wavelength campaign to study the Crab using Keck, Hubble Space Telescope (HST), and Chandra X-ray Observatory, the authors of [5] suggested the so-called "inner knot" to be just the emitting region for the flares.…”
Section: Introductionmentioning
confidence: 99%
“…The energy spectra of additional emission during the flares were measured to be different from those of the Nebula, however, "the mechanism driving the flares, their impulsive nature, the 12-month recurrence time, and the location, remain unknown" [5]. For all that, based on multi-wavelength campaign to study the Crab using Keck, Hubble Space Telescope (HST), and Chandra X-ray Observatory, the authors of [5] suggested the so-called "inner knot" to be just the emitting region for the flares. In addition, the analysis made by the AGILE collaboration for the September-October 2007 event has found a fine structure in the flare's time behavior [6].…”
Section: Introductionmentioning
confidence: 99%